Pengaruh Persepsi Mahasiswa Mengenai Uang Elektronik Terhadap Minat Menggunakan Aplikasi DANA - Lita Selvia; Nur Syamsiyah (Budgeting: Jurnal Akuntansi Syariah, 2023)
DANA or Indonesian Digital Wallet is an application-based digital payment service, where the application is available for the Android platform. The DANA application has many advantages that have been integrated with the Ministry of Home Affairs' Dukcapil (Civil Registry) system, but with the various advantages that the DANA application has, there are still many students who have not used the DANA application. For this reason, researchers want to study more about students' perceptions of electronic money on their interest in using the DANA application. This research uses quantitative methods. The analysis technique used is simple linear regression analysis. Data collection techniques using the questionnaire method as many as 67 respondents and the documentation method. The technique used in this research uses proportional random sampling technique. Proportional random sampling is said to be proportional, meaning that the sampling technique must be balanced in each stratum. Random means taking subjects randomly, so that each subject is considered the same. Where each class of members of the population can be selected randomly to become the research sample, by taking representatives from each class selected randomly, namely by lottery. The result of this study is that there is an influence on students' perceptions of electronic money on interest in using the DANA application with the results (t-test) obtained t_count 6.811 > t_table 1.997, while a significance value of 0.000 <0.05. (H_o is rejected and H_adi accepted). So it can be interpreted that students' perceptions of electronic money have a significant effect on interest in using the DANA application.